Female Empowerment and Survival in Damsel (2024): A Critical Analysis - Angreani Mangar; Indah Ramadhani Tehupali (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2026)
Film is widely recognized as a medium that reflects and shapes social values, particularly in the representation of gender roles and power relations. Although many modern films attempt to challenge traditional portrayals of women, there is still limited critical research that specifically examines how Damsel (2024) constructs themes of empowerment and resistance through character development and conflict. This study aims to analyze the transformation of the main character, Princess Elodie, and the role of conflict in shaping the narrative and its underlying social meanings. Using a qualitative descriptive approach, the data were collected from dialogues, character actions, and key scenes in the film. The data were analyzed through thematic analysis supported by theories of characterization, conflict, and feminist perspectives. The findings reveal that Elodie undergoes significant development from a passive and obedient figure into a strong, independent, and resilient individual. Both internal and external conflicts, including betrayal, survival, and psychological struggle, play a crucial role in driving this transformation. The study also finds that the film challenges patriarchal narratives by presenting a female protagonist who actively resists oppression and redefines her identity. Furthermore, symbolic elements such as the dragon and the cave reinforce themes of trauma, transformation, and justice. Overall, the film offers a reinterpretation of traditional fairy tales by emphasizing agency, resistance, and gender equality, contributing to contemporary discussions in film studies and cultural analysis.